A Rhodium(II)‐Catalyzed Formal [4+1]‐Cycloaddition toward Spirooxindole Pyrrolone Construction Employing Vinyl Isocyanates as 1, 4‐Dipoles. Issue 23 (3rd May 2017) - Meloche, Jennifer L.; Ashfeld, Brandon L.
Abstract: A Rh II ‐catalyzed, formal [4+1]‐cycloaddition between diazooxindoles as electrophilic C1 synthons and 1, 3‐heterodienes for the construction of spirooxindole pyrrolones is described. Employing vinyl isocyanates as 1, 4‐dipoles, the cycloannulation occurs under relatively mild conditions and provides the corresponding pyrrolones in good to excellent yields. Abstract : Put a ring on it : The title reaction between diazooxindoles as electrophilic C1 synthons and 1, 3‐heterodienes enables the construction of spirooxindole pyrrolones. Employing vinyl isocyanates as 1, 4‐dipoles, the cycloannulation occurs under relatively mild conditions and provides the corresponding pyrrolones in good to excellent yields.